Analysis of Sarcasm in Social Media Tweets Semantic Perspective - Leony Sitorus; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This study investigates the phenomenon of sarcasm in social media, particularly on Twitter, through a semantic and ethnographic lens. The aim is to explore how semantic cues—such as lexical choices, tone, and context—help users recognize sarcastic intent in written digital communication. Employing an ethnographic research design, this study observes linguistic behavior in natural online settings by collecting primary data from selected sarcastic tweets and secondary data from related linguistic and communication studies. Data were gathered using purposive sampling of tweets that explicitly exhibit sarcastic language, followed by contextual observation and discourse analysis. The findings indicate that sarcasm on Twitter commonly relies on exaggerated positivity used in negative or frustrating contexts, lexical contrast, ironic tone, and punctuation cues such as exclamation marks or quotation marks. These patterns are often used to signal meaning that contradicts the surface expression. The study highlights that understanding sarcasm requires more than decoding words—it demands cultural, contextual, and pragmatic awareness. The ethnographic approach provides insight into how online communities use shared knowledge and social cues to interpret sarcastic content. This research emphasizes the need for language sensitivity in digital communication to reduce misinterpretation and foster more effective online interaction.